Clozapine users in Australia: their characteristics and experiences of care based on data from the 2010 National Survey of High Impact Psychosis. (18th July 2016) - Siskind, D. J.; Harris, M.; Phillipou, A.; Morgan, V. A.; Waterreus, A.; Galletly, C.; Carr, V. J.; Harvey, C.; Castle, D.
Abstract : Aims: Clozapine is the most effective medication for treatment refractory schizophrenia. However, descriptions of the mental health and comorbidity profile and care experiences of people on clozapine in routine clinical settings are scarce. Using data from the 2010 Australian Survey of High Impact Psychosis, we aimed to examine the proportion of people using clozapine, and to compare clozapine users with other antipsychotic users on demographic, mental health, adverse drug reaction, polypharmacy and treatment satisfaction variables. Methods: Data describing 1049 people with a diagnosis of schizophrenia or schizoaffective disorder, who reported taking any antipsychotic medication in the previous 4 weeks, were drawn from a representative Australian survey of people with psychotic disorders in contact with mental health services in the previous 12 months. We compared participants taking clozapine ( n = 257, 22.4%) with those taking other antipsychotic medications, on a range of demographic, clinical and treatment-related indicators. Results: One quarter of participants were on clozapine. Of participants with a chronic course of illness, only one third were on clozapine. After adjusting for diagnosis and illness chronicity, participants taking clozapine had significantly lower odds of current alcohol, cannabis and other drug use despite similar lifetime odds. Metabolic syndrome and diabetes were more common among people taking clozapine; chronic pain was less common. Psychotropic polypharmacy did not differ between groups. Conclusions: Consistent with international evidence of clozapine underutilisation, a large number of participants with chronic illness and high symptom burden were not taking clozapine. The lower probabilities of current substance use and chronic pain among clozapine users warrant further study.